Contrasting patterns of allochthony among three major groups of crustacean zooplankton in boreal and temperate lakes. Issue 7 (1st July 2014) - Berggren, Martin; Ziegler, Susan E.; St-Gelais, Nicolas F.; Beisner, Beatrix E.; del Giorgio, Paul A.
Abstract : The importance of terrestrial‐derived organic matter for lake zooplankton communities remains debated, partly because little is known about the basic pathways by which allochthonous carbon is transferred to zooplankton, and whether these vary among the major taxonomic and functional groups. We quantified allochthony of three zooplankton groups ( Cladocera, Calanoida, and Cyclopoida ) across 18 lakes in Québec, spanning broad gradients of dissolved organic matter (DOM) and lake trophy, using a multi‐isotope (δ 2 H + δ 13 C), multi‐source (terrestrial, phytoplanktonic, benthic) approach. All three zooplankton groups had significant levels of allochthony, but differed greatly in their respective patterns across lakes. Allochthony in Calanoida and Cyclopoida was linked to detrital food chains based on particulate organic matter (POM) and on DOM, respectively, whereas in Cladocera it appeared related to both pathways; not surprisingly this latter group had the highest mean allochthony (0.31; compared to 0.18 in Cyclopoida and 0.16 in Calanoida ). This study highlights the complexity of the pathways of delivery and transfer of terrestrial organic matter in freshwaters, and underscores the role that microbial food webs play in this transfer.